Extreme hydroclimatic events and response of vegetation in the eastern QTP since 10 ka - Ren Weihe; Liu Zijian; Li Quan; Yi Guitian; Qin Feng (Open Geosciences)
Climate variations during the Holocene significantly impacted vegetation dynamics in the eastern Qinghai-Tibet Plateau (QTP). However, vegetation evolution in response to regional climatic trends and events during this interval remains controversial. Here, we present well-dated decadal-resolution loss on ignition (LOI) and grain size records from the Xing Co Lake on the eastern QTP. The records show an overall drying trend since 10 thousand years ago (ka), with multiple extreme precipitation events observed during 10 to 7 ka. An extreme drought event occurred at around 5.5 ka, after which the climate was drier and unstable with several drought events. In comparison with the hydroclimate, insolation, and El Niño Southern Oscillation records, our data show a close correspondence with the summer insolation differential between 30°N and 30°S and El Niño events on orbital-millennium timescales. This suggested that the increased rainfall during the early Holocene on the eastern QTP can be attributed to the high insolation differential between 30°N and 30°S and low El Niño events. Conversely, the drying trend in the late Holocene appears to correlate with a low insolation differential and high El Niño events. Whenever ice-rafted debris events occurred in the North Atlantic, there was a corresponding occurrence of drying events in the late Holocene in the Zoige Basin. This suggested that teleconnection between the precipitation on the eastern QTP and the North Atlantic climate exists in the Holocene. When compared to independent hydroclimatic and arboreal pollen (AP%) records on the eastern QTP, the evolutionary trends and events of AP% align closely with local hydroclimate changes. This suggested that arboreal coverage could rapidly respond to climate change during the Holocene, but further studies are needed.